A compact zeroth‐order directional antenna. Issue 4 (April 2014) - Dinesh, R.; Vinod, V. K. T.; Anila, P. V.; Jithin, P.; Deepak, C. M.; Mohanan, P.
Abstract A novel via free, asymmetrical coplanar strip fed zeroth‐order directional antenna suitable for 2.4 GHz WLAN applications is presented. The zeroth‐order resonance is achieved by realizing a composite right/left‐handed transmission line‐based interdigital capacitor inserted into the shorted asymmetric coplanar strip. The structural asymmetry provides an improved directivity for the antenna. The prototype made on a low cost substrate of relative permittivity 3.7 and height 1.6 mm with an overall dimension 29 × 16.5 × 1.6 mm3 offers a 2:1 VSWR impedance bandwidth of 280 MHz (2.21–2.49 GHz) and exhibits directional radiation pattern with a peak gain of 3.7 dBi over the entire operating band. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:929–932, 2014